The Impacts of Revd John Wesley’s Life and Ministry on England and Beyond: A Reflection - Amanambu, Uchenna Ebony (Journal of religion and human relations, 2020)
A careful study into the lives and activities of some of the great individuals who have changed the lives and conditions of humanity reveals that they had some striking features. The likes of Martin Luther, Mahatma Gandhi, and Martin Luther King Jr among others have some things in common. Interestingly, those things they have in common usually serve as the driving force in their struggles. One of those striking features is their thirsts for the upliftment of human person. Unequivocally, Rev John Wesley’s life and his ministry can be grouped among these men. He made a strong and commanding impact on the general affairs of eighteenth century England and by extension, the world in general. His life and ministry have impacted so much on the socioeconomics, moral, religious and political transformation of the eighteenth century England and the world in general. Nothing has helped bring mankind out of conundrum like men who understood and vigorously pursued their visions and these visions usuallytranslate into their mission.